Environmental Health Risk Analysis of TSP and PM10 Exposure to Communities Around Coal Mining - Muhammad Isra Ahdyannor; Muliyadi Saputra (Nusantara Sehat: Jurnal Kesehatan Indonesia, 2026)
ABSTRACT The coal mining industry contributes to the emission of Total Suspended Particulate (TSP) and Particulate Matter 10 (PM10) dust which has the potential to disrupt the health of the surrounding community. The main problem with this study is that the level of health risk due to exposure to dust is not yet known in detail. The purpose of the study was to analyze the level of non-carcinogenic health risks from TSP and PM10 exposure in communities around coal mining areas. The research used the Environmental Health Risk Analysis (ARKL) method. The population is the community around the mine with samples taken at four points of air measurement locations. Sampling was carried out by taking TSP and PM10 concentration data. The research variables included dust concentration, anthropometric characteristics and respondent activity patterns. Data were collected using dust measuring tools as well as interview questionnaires and analyzed using the RQ approach for risk characterization. The Risk Quotient (RQ) values for the TSP parameter range from 0.002 to 0.010 and for PM10 range from 0.1166 to 0.7876, all of which are still below the risk threshold (RQ < 1). This shows a low non-carcinogenic risk to the community around the mine. However, monitoring and control efforts are still necessary especially at points with the highest PM10 RQ values that are close to safe limits. Effective risk management through dust source control, use of personal protective equipment, periodic monitoring, and public education must continue to be optimized to maintain public health and minimize potential impacts in the future. Keywords: ARKL, RQ, Coal Mining, PM10, TSP